2020
DOI: 10.3390/genes11040382
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Splice Site Mutation in ZP1 Causes Familial Oocyte Maturation Defect

Abstract: In vitro fertilization (IVF) involves controlled ovarian hyperstimulation using hormones to produce large numbers of oocytes. The success of IVF is tightly linked to the availability of mature oocytes. In most cases, about 70% to 80% of the oocytes are mature at the time of retrieval, however, in rare instances, all of them may be immature, implying that they were not able to reach the metaphase II (MII) stage. The failure to obtain any mature oocytes, despite a well conducted ovarian stimulation in repeated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Without strong functional data, it is always difficult to formally conclude that a missense variant is deleterious. Here, we have three strong arguments that permit to conclude without any doubt that the identified variant is responsible for the patient's infertility: (i) several publications have linked ZP1 defects with OMD and several missense variants were postulated to be deleterious 21 (Table 2); (ii) the identified variant is predicted by 20 out of 25 prediction softwares to be deleterious and (iii) this very rare variant is found in five affected subjects and the difference in the variant frequency between the patients' group and a control population is most highly significant (p. value = 2EÀ31). As all patients had the same mutation and all came from the same geographical region, we can expect them to have a common ancestor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Without strong functional data, it is always difficult to formally conclude that a missense variant is deleterious. Here, we have three strong arguments that permit to conclude without any doubt that the identified variant is responsible for the patient's infertility: (i) several publications have linked ZP1 defects with OMD and several missense variants were postulated to be deleterious 21 (Table 2); (ii) the identified variant is predicted by 20 out of 25 prediction softwares to be deleterious and (iii) this very rare variant is found in five affected subjects and the difference in the variant frequency between the patients' group and a control population is most highly significant (p. value = 2EÀ31). As all patients had the same mutation and all came from the same geographical region, we can expect them to have a common ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous ZP mutations have been identified in infertile women with diverse types of infertilities such as PCOS (ZP4, 28 ), endometriosis ( ZP4 , 29 ), unexplained IVF attempts failures ( ZP1 30–32 ; ZP2 31,33 ; ZP3 32,34 ), OMD ( ZP1 21 ) and mainly with the Empty Follicle Syndrom (EFS) pathology ( ZP1 29,33,35–39 ; ZP2 29,38 and ZP3 29,40,41 ). Interestingly, the ZP1 gene is the most mutated ZP gene and an overview of the 27 ZP1 mutations according to the patients' clinical manifestations and to their position on the gene sequence and on the protein is shown in Table 2 and Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abnormal ZP morphology observed in oocytes has been reported by several investigators. Notably, a recent report by Okutman et al (2) reported a homozygous splice site mutation (c.1775-3C>A) in the ZP1 gene associated with familial oocyte maturation arrest.…”
mentioning
confidence: 99%